The Bauhaus and us - Cseke, Fruzsina; Májer, Viktória (ARTCADIA, 2022)
This description reflects on the events of the Bauhaus centenary from a student's point of view. As former students (Painting and Graphics Studies), the two authors were active participants in the programmes, working on many courses with Bauhaus tasks. In their writing, they recall the experiences of these semesters: the most interesting exercises, creations, challenges and methods.
Keywords: contemporary art education; colour star; reflection; Bauhaus celebrations; experience-based learning